Development of amino acid substituted gemini surfactant-based mucoadhesive gene delivery systems for potential use as noninvasive vaginal genetic vaccination. (February 2015) - Singh, Jagbir; Michel, Deborah; Getson, Heather M; Chitanda, Jackson M; Verrall, Ronald E; Badea, Ildiko
Aim: Recently, we synthesized amino acid- and peptide-substituted gemini surfactants, 'biolipids' that exhibited high transfection efficiency in vitro . In this study, we developed these plasmid DNA and gemini surfactant lipid particles for noninvasive administration in vaginal cavity.Material & methods: Novel formulations of these gene delivery systems were prepared with poloxamer 407 to induce in situ gelling of the formulation and diethylene glycol monoethyl ether to improve their penetration across mucosal tissue.Results: Poloxamer at 16% w/v concentration in diethylene glycol monoethyl ether aqueous solution produced dispersions that gelled near body temperature and had a high yield value, preventing leakage of the formulation from the vaginal cavity. Intravaginal administration in rabbits showed that the glycyl-lysine-substituted gemini surfactant led to a higher gene expression compared with the parent unsubstituted gemini surfactant.Conclusion: This provides a proof-of-concept that amino acid substituted gemini surfactants can be used as noninvasive mucosal (vaginal) gene delivery systems to treat diseases associated with mucosal epithelia.